Factors structuring the spatial distribution of Chironomidae larvae community in the floodplain of the northern Pantanal, Brazil - Santos,Maitê Tambelini dos (2013)
AIM: In order to identify the factors structuring the spatial distribution of the Chironomidae community, we analyzed the effects of water and sediment characteristics, flood duration and type of phytophysiognomic unit on the taxa composition of this community. MÉTODOS: O estudo foi realizado em 26 parcelas do Sítio de Amostragem de Longa Duração (SALD), localizado em uma área sazonalmente inundável na parte norte do Pantanal (Brasil). The study was conducted at 26 plots of the Long-Term Sampling Site, located in a seasonally flooded area in northern Pantanal (Brazil). Sediment samples were taken from each plot to analyze the Chironomidae community, organic matter and particle size; limnological parameters (depth, water temperature, dissolved oxygen, electrical conductivity and pH); besides the duration of flood. RESULTS: We identified 432 individuals distributed into 21 Chironomidae taxa. Polypedilum and Ablabesmyia were the most frequent spatially. The multivariate multiple regression analysis showed that the community composition was significantly related to the flood duration and grain size characteristics, but not to phytophysiognomic units and limnological parameters. Plots with predominantly sandy substrate and flooded for a shorter time presented a greater occurrence of taxa. CONCLUSIONS: The gradient produced by the spatial distribution of sediment grain size and flood duration determined the distribution of Chironomidae taxa. Changes in the hydrological functioning of the Pantanal, such as those from reservoir construction in the uplands region and roads and dykes construction in the floodplain could then impact the local chironomid biodiversity.